Place, Time, and Conditions in the Art of Intercultural Dialogue - Diane Butler (IAHN-TP Palangka Raya, 2022)
How can mutual understanding and exchanges among people of different cultures and ethnicities be supported in a manner that recognizes the variety of their worldviews and spatial-temporal-kinesthetic knowledge and cultural and spiritual values? In my experience, a practice-based approach to the art of intercultural dialogue does not stem from a predetermined method but rather is an organic process that grows from the interactions of the people involved, which will evolve differently in each place depending on its historical and current conditions. One approach that I have greatly appreciated in Indonesia, which has given good results, is by taking into account the place, time and conditions. With this in mind, I will share some aspects one might consider in the fostering of a common field for dialogue.